Analisis Sistem Pendukung Keputusan Penentuan Penerima Beasiswa Menggunakan Metode SAW dan AHP - Rakhma Sarita; Lukman Bachtiar (Universitas Budi Darma, 2022)
Scholarship is one of the allowances given to students as study aid provided by the government. Likewise with the Kotawaringin Timur government, which annually provides scholarship assistance to students with limited conditions and quotas. Formal educational institutions under the auspices of the Kotim Regency Education Office, students or college students get a quota for those participating in the scholarship program for underprivileged and high achieving criteria from the government. Therefore, scholarships must be given to students who deserve and deserve to get it in accordance with the regulations that have been set at the Kotim Regional Secretariat office. This selection process requires accuracy and a long time, because each data is compared with each other according to predetermined criteria. This study resulted in the final value of the comparison between the SAW and AHP methods. The final result with the SAW method the highest value obtained by the fifth alternative with 100. While the final result with the AHP method obtained the highest value by A1 with a value of 0.4734.